Local Injections of Tacrolimus-loaded Hydrogel Reduce Systemic Immunosuppression-related Toxicity in Vascularized Composite Allotransplantation. Issue 10 (October 2018) - Dzhonova, Dzhuliya V.; Olariu, Radu; Leckenby, Jonathan; Banz, Yara; Prost, Jean-Christophe; Dhayani, Ashish; Vemula, Praveen K.; Voegelin, Esther; Taddeo, Adriano; Rieben, Robert
Abstract : Background: Routine application of vascularized composite allotransplantation is hampered by immunosuppression-related health comorbidities. To mitigate these, we developed an inflammation-responsive hydrogel for local immunosuppression. Here, we report on its long-term effect on graft survival, immunological, and toxicological impact. Methods: Brown Norway-to-Lewis rat hindlimb transplantations were treated either systemically with daily injections of 1 mg/kg tacrolimus (TAC) or with subcutaneous intragraft injections of hydrogel containing 7 mg TAC, every 70 days. Animals were monitored for rejection or other pathology for 280 days. Systemic and graft TAC levels, regulatory T cells, and donor cell chimerism were measured periodically. At endpoint, markers for kidney, liver, and metabolic state were compared to naive age-matched rats. Results: Both daily systemic TAC and subcutaneous intragraft TAC hydrogel at 70-day intervals were able to sustain graft survival longer than 280 days in 5 of 6 recipients. In the hydrogel group, 1 graft progressed to grade 3 rejection at postoperative day 149. In systemic TAC group, 1 animal was euthanized due to lymphoma on postoperative day 275. Hydrogel treatment provided stable graft and reduced systemic TAC levels, and a 4 times smaller total TAC dose compared with systemic immunosuppression. Hydrogel-treated animals showed preserved kidney function, absence of malignancies or opportunistic infections and increased hematopoietic chimerism compared with systemic immunosuppression. Conclusions: Our findings demonstrate that localized immunosuppression with TAC hydrogel is a long-term safe and reliable treatment. It may reduce the burden of systemic immunosuppression in vascularized composite allotransplantation, potentially boosting the clinical application of this surgical intervention. Abstract : Dzhonova et al document the ability of locally delivered tacrolimus within hydrogels, every 70 days, to sustain allogeneic hind limb survival in a Brown Norway-to-Lewis rat model. Local delivery reduced systemic tacrolimus levels and drug toxicity compared to daily injections. Supplemental digital content is available in the text.